Tapping the Potential of Energy Efficiency to Create Greater Economic Security for Maine - Voorhees, Dylan (Maine Policy Review, 2008)
Energy efficiency is cheaper than any current sources of power or fuel. Maine has started to develop some energy-efficiency programs such as Efficiency Maine and MaineHousing’s weatherization efforts, but the state lags behind other states in the region. Dylan Voorhees addresses barriers that Maine needs to overcome in order to tap its energy-efficiency potential. He suggests an expanded strategy, including planning for the long term, leveraging private investments and taking advantage of the private sector, extending efficiency programs to all fuels, and consolidating current energy-efficiency planning and budgeting
Keywords: Maine; energy efficiency; energy policy